Stolen in her wedding gown - Cinelli, Amanda (Harlequin presents, 2021)
"About to walk down the aisle of her Manhattan wedding, determined Priya realizes it's impossible. After the news Greek playboy Eros has just shared about her convenient groom, she can't go through with it. To save her father's business, she flees in her white dress... and weds Eros instead! To beat his brother to the family inheritance, Eros must stay married for one year. Stealing Priya as his wife was the first step. The he discovers her deepest secrets -- and a burning mutual desire. What started as convenient suddenly got very complicated..." --